1991
DOI: 10.1126/science.1719635
|View full text |Cite
|
Sign up to set email alerts
|

GPI-Anchored Cell-Surface Molecules Complexed to Protein Tyrosine Kinases

Abstract: Binding of ligand or antibody to certain cell-surface proteins that are anchored to the membrane by glycophosphatidylinositol (GPI) can cause activation of leukocytes. However, it is not known how these molecules, which lack intracellular domains, can transduce signals. The GPI-linked human molecules CD59, CD55, CD48, CD24, and CD14 as well as the mouse molecules Thy-1 and Ly-6 were found to associate with protein tyrosine kinases, key regulators of cell activation and signal transduction. A protein tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
516
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 818 publications
(542 citation statements)
references
References 14 publications
24
516
1
1
Order By: Relevance
“…Since CD24 is localized in lipid rafts, the absence or presence of CD24 may influence membrane raft composition and thereby affect important signaling pathways within the cell (37). It has also been reported that CD24 is involved in intracellular signaling by direct binding to tyrosine kinases (38).…”
Section: Discussionmentioning
confidence: 99%
“…Since CD24 is localized in lipid rafts, the absence or presence of CD24 may influence membrane raft composition and thereby affect important signaling pathways within the cell (37). It has also been reported that CD24 is involved in intracellular signaling by direct binding to tyrosine kinases (38).…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to occur via direct protein-protein interactions between caveolins and signaling components found at the plasma membrane. In various cell types, caveolin proteins have been shown to be associated with G protein-coupled receptors, G protein subunits, tyrosine kinase receptors, various intracellular kinases, voltage-gated ion channels, ion pumps, and various second messenger molecules [42][43][44][45].…”
Section: Caveolins: Important For the Trafficking And Clustering Of Mmentioning
confidence: 99%
“…By preferentially including some proteins and excluding others, lipid rafts and related membrane microdomains such as caveolae may regulate the sorting and trafficking of certain plasma membrane proteins and lipids and compartmentalize cell-signaling events (Verkade and Simons, 1997;Anderson, 1998;Brown and London, 1998;Horejsi et al, 1999). Although lipid rafts have been inferred from functional and kinetic studies of intact cells (Mays et al, 1995;Hannan and Edidin, 1996;Sheets et al, 1997;Keller and Simons, 1998), most evidence of their existence is based on differential extraction of cells with detergent (Skibbens et al, 1989;Stefanova et al, 1991;Brown and Rose, 1992;Fiedler et al, 1993;Sargiacomo et al, 1993). These studies indicate that in addition to GSL and cholesterol, lipid rafts are enriched in GPI-anchored proteins, some transmembrane proteins, and diacylated cytoplasmic proteins including Src family kinases.…”
Section: Introductionmentioning
confidence: 99%